Advice on the Management of Ambiguous Genitalia to a Young Endocrinologist from Experienced Clinicians - Wilson, Jean D.; Rivarola, Marco A.; Mendonca, Berenice B.; Warne, Garry L.; Josso, Nathalie; Drop, Stenvert L.S.; Grumbach, Melvin M. (Seminars in Reproductive Medicine, 2012)
The birth of a child with ambiguous genitalia is a challenging and distressing event for the family and physician and one with life-long consequences. Most disorders of sexual differentiation (DSD) associated with ambiguous genitalia are the result either of inappropriate virilization of girls or incomplete virilization of boys. It is important to establish a diagnosis as soon as possible, for psychological, social, and medical reasons, particularly for recognizing accompanying life-threatening disorders such as the salt-losing form of congenital adrenal hyperplasia. In most instances, there is sufficient follow-up data so that making the diagnosis also establishes the appropriate gender assignment (infants with congenital adrenal hyperplasia, those with androgen resistance syndromes), but some causes of DSD such as steroid 5α-reductase 2 deficiency and 17β-hydroxysteroid dehydrogenase deficiency are associated with frequent change in social sex later in life. In these instances, guidelines for sex assignment are less well established.
Keywords: disorders of sexual development (DSD); Jost model; anti-Müllerian hormone; testosterone; dihydrotestosterone; chromosomal sex; gonadal sex; phenotypic sex; androgen insensitivity; congenital adrenal hyperplasia (CAH); placental aromatase deficiency; ovotesticular DSD; defects in androgen synthesis/action; 5α-reductase 2 deficiency; mixed gonadal dysgenesis